2005
DOI: 10.1152/jn.01163.2004
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Currents in Isolated Statocyst Neurons and RPeD1 in the Pond Snail,Lymnaea stagnalis

Abstract: To begin to determine the underlying neural mechanisms of memory formation, we studied two different cell types that play important roles in different forms of associative learning in Lymnaea. Statocyst neurons (hair cells) mediate classical conditioning, whereas RPeD1 is a site of memory formation induced by operant conditioning of aerial respiration. Because potassium (K(+)) channels play a critical role in neuronal excitability, we initiated studies on these channels in the aforementioned neurons. Three dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 33 publications
(30 reference statements)
0
11
0
Order By: Relevance
“…Based on current clamp condition we found that Pimpinella anisum essential oil led to a decrease in the amplitude of AHPs. In snail neurons, spike repolarization and AHP are determined by a set of potassium channels which underlie fast and delayed K + outward currents (Thompson, 1977;Solntseva, 1995;Bal et al, 2000Bal et al, , 2001Sakakibara et al, 2005), and also two classes of Ca 2+ activated K + channels; large conductance Ca 2+ activated K + channels (BK channels) and small conductance Ca 2+ activated K + channels (SK channels) (Hermann and Erxleben, 1987;Gola et al, 1990;Crest and Gola, 1993). In many neurons, Ca 2+ influx through voltage dependent Ca 2+ channels and consequent activation of Ca 2+ dependent potassium channels is a major determinant of AHP amplitude and duration.…”
Section: Discussionmentioning
confidence: 99%
“…Based on current clamp condition we found that Pimpinella anisum essential oil led to a decrease in the amplitude of AHPs. In snail neurons, spike repolarization and AHP are determined by a set of potassium channels which underlie fast and delayed K + outward currents (Thompson, 1977;Solntseva, 1995;Bal et al, 2000Bal et al, , 2001Sakakibara et al, 2005), and also two classes of Ca 2+ activated K + channels; large conductance Ca 2+ activated K + channels (BK channels) and small conductance Ca 2+ activated K + channels (SK channels) (Hermann and Erxleben, 1987;Gola et al, 1990;Crest and Gola, 1993). In many neurons, Ca 2+ influx through voltage dependent Ca 2+ channels and consequent activation of Ca 2+ dependent potassium channels is a major determinant of AHP amplitude and duration.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Lymnaea indicated the presence of two types of pharmacologically distinct K channels: one sensitive to TEA and the other to 4AP. They have been shown to contribute to different phases of action potential repolarization (Sakakibara et al, 2005). The perfusion of a cocktail of 20 mM TEA and 5 mM 4AP, concentrations that have been suggested to be effective to block both K channels in Helisoma and Lymnaea (Berdan and Easaw, 1992;Staras et al, 2002), caused a decrease in firing frequency by 34.5 ± 2.7% (n = 7, P < 0.05) combined with an increase in action potential amplitude by 21.5 ± 0.3% (n = 7, P < 0.05) (Fig.…”
Section: K Channels Mediate the Da-induced Hyperpolarizing Effectmentioning
confidence: 99%
“…Whole-cell patch-clamp recordings in the Lymnaea neuron were made using a multiclamp 700 A amplifier (Axon Instruments) [26,27]. Patch electrodes (tip diameter adjusted to 1.0 lm; resistance, 1-3 MX) were pulled from glass tubing (outside diameter, 1.5 mm) with no filament (PG-150T-7.5; Warner Instrument, Hamden, CT, USA) on a vertical pipette puller (PA-10; Narishige, Tokyo, Japan).…”
Section: Membrane Resistance Measurement By Patch-clamp Recordingsmentioning
confidence: 99%